Relationship between cylinder and core compressive strength - Bisher, Hamood (University of Science and Technology, Sana'a, 2010)
The main objective of this paper is to report the results of an experimental study conducted to obtain the relationship between the compressive strengths of concrete cylinders and cores made using four different water-cement ratios, two cement contents, and two different types of aggregates. The strength results of cast and cored cylindrical specimens were compared and correlated to each other. It was found that the linear relationship between the cylinder and core compressive strength is very significant and almost independent of the mixture parameters.